Political, Social and Economic Determinants of Corruption - Ghaniy, Nafi; Hastiadi, Fithra Faisal (International Journal of Economics and Financial Issues, 2017)
This study aims to analyze various political, social and economic determinants, measured through development indicators and various indexes, upon the perceived level of corruption indicated by corruption perception index in 92 observed countries for the year of 2014. The results prove that level of development, degree of democracy, economic freedom, level of education, political stability and religion have significant impact on the perceived level of corruption. Yet, there are differences in significant variables between the developing and developed countries groups. Keywords: Corruption, Economic Development, GDP per capita JEL Classifications: O17, O10, O11